Transformative Arts Practices in the Criminal Justice System. The impact of human rights violations on identity amongst those previously incarcerated - Adams, Nawaal (Department of Drama, 2024)
This research discusses the impact that human rights violations have on the identity of parolees and ex-offenders. It makes use of the Applied Theatre form, Theatre of the Oppressed (TO), and its practices of Image Theatre and Newspaper Theatre. These practices draw on lived experiences in the form of storytelling and poetry, based on metaphor and its links with reality. The writing in the research is defined as autobiographical fiction or autofiction and becomes performative using TO. The core aim of this research and its process is to rewrite, redefine, or reclaim identity through performative autofiction. It unpacks the human rights violations experienced by the incarcerated, using evidence from various resources including case studies and fieldwork with members of the Second Chance Theatre Project (Cape Town). The research process explored individual identity, relational identity, collective identity, and material identity. This research opens a discussion on the current South African criminal justice system and its failure to uphold ratified policies and programmes. It suggests a discourse that could be delivered through the vocal and physical body.